A lei de acesso à informação em portais de transparência governamentais brasileiros - Walisson da Costa Resende (2014)
The core objective of this research was to evaluate a given group of Brazilian government Transparency Portals in line with the applicable regulations and recommendations made by the Federal Office of the Comptroller General from the standpoint of Information Management. The methodology was based on a qualitative survey of 27 Transparency Portals maintained by Brazilian state administrations. The evaluation of each portal took into account the criteria and recommendations issued by the Federal Office of the Comptroller General in 2013. Moreover, each state portal was compared to the Federal Administrations Transparency Portal, which was taken as a benchmark. The necessary theoretical framework to conduct such analyses comprises official documents from the Brazilian government entities, like the federal administration and the Office of the Comptroller General; studies published by authors who have already dealt with the recently enacted Information Access Act; traditional academic studies on Knowledge and Information Management; and the relations among Information Management, the Information Access Act and Public Transparency Portals. The study results indicate that most Transparency Portals maintained by Brazilian state administrations do not fully comply with the provisions of the federal Information Access Act and the recommendations made by the Federal Office of the Comptroller General. Such Portals do not show strict correspondence with the benchmark portal, i.e. the Federal Transparency Portal, either. The deficiencies found in the implementation of such portals have led to zones of information opacity in an environment that was supposed to feature utmost transparency.